Impact of non-motor symptoms in Parkinson’s disease: a PMDAlliance survey - Hermanowicz N; Jones SA; Hauser RA (Neuropsychiatric Disease and Treatment, 2019)
Neal Hermanowicz,1 Sarah A Jones,2 Robert A Hauser31Department of Neurology, Parkinson’s Disease and Movement Disorders Program, University of California, Irvine, CA, USA; 2Parkinson and Movement Disorder Alliance (PMDalliance), Tucson, AZ, USA; 3Department of Neurology, USF Health Parkinson’s Disease and Movement Disorders Center, Parkinson Foundation Center of Excellence, Tampa, FL, USAPurpose: Parkinson’s disease (PD) is associated with non-motor symptoms (NMS) that can cause progressive disability and impact quality of life of people with PD (PwP) and increase burden on care partners. This survey was designed to evaluate the prevalence, impact, and educational preferences regarding NMS on PwP and their care partners.Patients and methods: A 17-question survey was sent to the total membership of PMDAlliance, a nonprofit organization reaching 3,685 households of PwP. Care partners and other interested individuals could also respond. The survey was conducted using Survey Monkey, an online survey platform, and included distinct questions for respondents with and without NMS.Results: A total of 700 individuals responded to the survey. Of the respondents, 378 (54%) were care partners and 287 (41%) were PwP. About 90% of the respondents reported having experience with NMS in PwP, including sleep problems (84%), cognitive symptoms (76%), anxiety (65%), depression (56%), hallucinations (40%), and delusions (23%). NMS in PwP were reported by more care partners (97%) than PwP (80%). NMS had at least some impact on quality of life for 84% of the respondents; 48% indicated that NMS represented a greater challenge than motor symptoms. Care partners were more likely than PwP to report that NMS were more challenging than motor symptoms (58% vs 32%). Respondents with and without NMS indicated a desire for NMS education.Conclusion: This survey underscores the significant impact of NMS on the quality of life of PwP and highlights the need for improved recognition and education about its effects.Keywords: sleep, cognition, anxiety, depression, hallucinations, delusions, treatment